IGF1-R inhibition and liposomal doxorubicin: Progress in preclinical evaluation for the treatment of adrenocortical carcinoma. (15th June 2016) - Beuschlein, Felix; Jakoby, Judith; Mentz, Susanne; Zambetti, Gerard; Jung, Sara; Reincke, Martin; Süss, Regine; Hantel, Constanze
Abstract: Adrenocortical carcinoma (ACC) is a tumor with poor prognosis and limited therapeutic options. Therefore, in addition to multi-chemotherapeutic regimens IGF-1 receptor (IGF-1R) targeting approaches have been evaluated including immunoliposomal (IL) preparations utilizing an IGF-1R inhibiting antibody. In the current study, we extended our experiments by long-term treatment regimens in the classical adrenocortical NCIH295R xenograft model as well as by short-term experiments in two novel xenograft models, which all displayed different levels of IGF-1R and IGF-2 expression. Interestingly, these experiments reveal sub-group dependent differences in therapeutic outcome, reflecting clinical observations and indicate, thus, that implementation of this panel of tumor models might be helpful for clinical translation of novel therapeutic regimens in the future. Highlights: We established novel approaches of IGF-1 receptor inhibition and liposomal doxorubicin for therapeutic treatment of adrenocortical carcinoma. We investigated therapeutic responsiveness in three different xenograft models for ACC (NCI-H295R, SJ-ACC3, MUC-1). Our experiments indicate, that implementation of this panel of tumor models might be helpful for clinical translation in the future.